Monoclonal antibody defines CA 19-9 in pancreatic juices and sera. Issue 5 (May 1985) - Schmiegel, W H; Kreiker, C; Eberl, W; Arndt, R; Classen, M; Greten, H; Jessen, K; Kalthoff, H; Soehendra, N; Thiele, H G
Abstract : In a retrospective study pancreatic juice samples (n = 213) and corresponding serum samples (n = 110) were assayed for their concentration of monoclonal antibody defined CA 19-9/GICA (gastrointestinal cancer associated antigen). Serum CA 19-9 values were found to be good diagnostic and discriminating markers for pancreatic disorders and were raised (greater than 50 u/ml) in more than 80% of the pancreatic cancer patients compared to 8.5% of the pancreatitis group and none of the control group. In contrast pancreatic juice CA 19-9 values showed a considerable overlap between groups. On the basis of recent molecular data on the monoclonal antibody 19-9 defined antigen(s)–that is, monosialoganglioside, mucin–it is proposed that the discrepancies between serum and pancreatic juice findings are due to a specific undirected endocrine release of the mucin into sera in pancreatic tumour patients while in pancreatic juices of all diagnostic groups high CA 19-9 activities are either owing to coexistence of glycolipid and mucin or that the latter is a physiologically exocrine product.